The Effect of Liquid Smoke on Scabies Pain and Wound among Students at Islamic Boarding School - Nursalam, Nursalam; Mahmudah, Ika Zulkafika; Has, Eka Misbahatul Marah (International Journal of Psychosocial Rehabilitation, 2020)
Scabies is one of the skin diseases frequently experienced by students at Islamic boarding schools. Almost all Scabies medication has a side effect, such as irritation. Liquid smoke from coconut shells contains analgesic, anti-inflammatory, antimicrobial, and antioxidant properties that benefit the process of wound healing. This study aimed to analyze the effect of liquid smoke from coconut shells on scabies pain and wound. This was a quasi-experiment study. The sample used was 60 students at an Islamic Boarding School. The samples were divided into two groups (intervention and control). The independent variable was topical liquid smoke for 14 days, while the dependent variable was the level of pain and the process of wound healing. Data were collected by using a questionnaire and wound observation. The results showed that there were significant differences between the intervention and control groups (p = 0,000) based on the Mann-Whitney test. There were significant differences between the treatment and control groups in the wound healing process with erythema criteria (p = 0,000), lesions (p = 0,000), granulation (p = 0,000), and scabies hole closure (p = 0,000) based on the Mann-Whitney test. Topical liquid smoke from coconut shells can decrease the level of pain and accelerate the process of scabies wound healing. Future studies can analyze the effect of liquid smoke on other skin diseases.